2018
DOI: 10.1016/j.rmed.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver and pediatric provider perspectives on symptom-based inhaled corticosteroid therapy in asthma

Abstract: SBA was generally viewed favorably by caregivers and providers of African American children. However, concerns regarding effectiveness of SBA were voiced by both caregivers and providers. Patient education and provider-patient communication is important in implementing this alternative asthma management strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This is similar to other studies 13,37 whereby parents tried various ways to improve children's asthma control, such as the use of CAM and the home nebuliser. Parents feared the use of preventer medication for asthma would cause side effects and dependency, a common concern in Asian and western countries [38][39][40] . However, the use of CAMs without proper monitoring and over-reliance on the use of nebuliser at home could potentially lead to delay in seeking treatment, causing morbidity and even mortality 41 .…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to other studies 13,37 whereby parents tried various ways to improve children's asthma control, such as the use of CAM and the home nebuliser. Parents feared the use of preventer medication for asthma would cause side effects and dependency, a common concern in Asian and western countries [38][39][40] . However, the use of CAMs without proper monitoring and over-reliance on the use of nebuliser at home could potentially lead to delay in seeking treatment, causing morbidity and even mortality 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting this approach comes from recent clinical trials that demonstrated the clinical equipoise between a symptom-driven ICS/LABA treatment strategy and traditional therapy (30)(31)(32)(33). However, prior studies have opined that providers are unaware of or skeptical of these latest recommendations (34,35).…”
Section: Update In 2019 Asthma Recommendationsmentioning
confidence: 99%
“…Evidence supporting this approach comes from recent clinical trials that demonstrated the clinical equipoise between a symptom-driven ICS/LABA treatment strategy and traditional therapy [33][34][35][36]. However, prior studies have opined that providers are unaware of or skeptical of these latest recommendations [37,38].…”
Section: Rationale For This Study Update In 2019 Asthma Recommendationsmentioning
confidence: 99%